Rapid evaluation of the rheological change caused by starch retrogradation with repeating freeze–thaw cycles. (25th May 2016) - Yamazaki, Eiji; Kubo, Tomoko; Umetani, Kaori; Fujiwara, Takayuki; Kurita, Osamu; Matsumura, Yasuki
Abstract : Dynamic oscillation rheometry in combination with repeating freeze–thaw (FT) cycles (DOR‐FT) was applied to evaluate the rheological change of starch gel caused by long‐term retrogradation. The gels prepared from corn, wheat, rice, potato, and sweet potato starch pastes (6%, w/w) were formed on a dynamic rheometer plate and the rheological changes induced by the FT cycles were measured while their gels remained on the rheometer plate. Comparing with the storage modulus ( G ′) at 25°C of each starch gels without FT, G ′ of corn, wheat, rice, potato, and sweet potato starch gels after three FT cycles increased by 341, 474, 167, 1368, and 631%, respectively. The DOR‐FT method enabled the evaluation of the rheological changes caused by the long‐term retrogradation within 1 h, which is much shorter than with the conventional puncture test. Moreover, G ′ versus FT cycles could be expressed as an exponential function model, indicating that the function model would show the FT cycle dependence for the rheological change of starch gels.